Evaluating damage in the perianth: a new diagrammatic scale to estimate population level of Aceria guerreronis Keifer (Acari: Eriophyidae) in coconut fruits - André Silva Guimarães Sousa; Manoel Guedes Correa Gondim Jr.; Poliane Sá Argolo; Anibal Ramadan Oliveira (Acta Agronómica, 2017)
The coconut mite, Aceria guerreronis Keifer (Acari: Eriophyidae), is one of the main pests of the coconut crop by attacking the fruits. Colonies can reach 10,000 mites/fruit at high infestation. A diagrammatic scale (Galvão scale) has been developed and tested by Brazilian researchers to estimate the number of mites/fruit by determining the percentage of necrotic area of the fruit surface. Our objective was to develop and validate a new diagrammatic scale based on the percentage of the damaged perimeter of the fruit at the base of the perianth, in order to facilitate and improve the quantification of A. guerreronis per fruit. Fruits were collected in an urban coconut plantation in Ilhéus, Bahia, Brazil. For the development of the new diagrammatic scale, it was calculated the percentage of the damaged perimeter on 50 fruits with different damage levels. To analyze the relationship between the damage and population levels of A. guerreronis on the fruits, we compared the two scales by testing them both on 470 fruits. The new diagrammatic scale recorded nine damage levels, 1, 2, 4, 8, 16, 32, 48, 70 and 100%. To validate our new diagrammatic scale, the damage level in each fruit was estimated by 10 inexperienced evaluators, with and without the aid of the scale. The accuracy and precision of each evaluator were determined through linear regression between observed and estimated damage. With or without or the use of the scale, 5 of 10 evaluators overestimated or underestimated the damage level and were imprecise and inaccurate. This showed that the scale did not provide improvements in the levels of accuracy and precision of the evaluators. The relationship between infestation and damage levels showed high accuracy for both scales in the regression analysis (R²= 96% and R²= 98%). The population peak of A. guerreronis by the new diagrammatic scale occurred at 32% of damage level and for the Galvão scale it occurred at 8% of damage level. Although the new diagrammatic scale has not promoted improvements in damage estimates, it presented high precision in the relationship between infestation and damage levels.